2006
DOI: 10.1007/s00418-006-0204-3
|View full text |Cite
|
Sign up to set email alerts
|

Zonal hierarchy of differentiation markers and nestin expression during oval cell mediated rat liver regeneration

Abstract: Oval cells constitute a heterogeneous population of proliferating progenitors found in rat livers following carcinogenic treatment (2-acetylaminofluorene and 70% hepatectomy). The aim of this study was to investigate the cellular pattern of various differentiation and cell type markers in this model of liver regeneration. Immunophenotypic characterisation revealed at least two subtypes emerging from the portal field. First, a population of oval cells formed duct-like structures and expressed bile duct (CD49f) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…[73][74][75] Immunohistochemistry of BDL livers demonstrated that some bile ductular cells expressed Ptc and Gli-2, suggesting that relatively immature liver epithelial cells are Hh targets. Our in vitro studies support this concept because, under our culture conditions, the Ptc-( þ )ve cholangiocyte line coexpressed several oval cell markers, mpk and c-kit, [44][45][46][47] and the immature cholangiocyte marker, N-CAM, 3,43,76,77 as well as markers of more mature cholangiocytes (ie, aquaporin-1 and CK-19). If further research verifies that Hh signaling promotes the outgrowth of relatively immature liver epithelial cells, this might explain why patchy lobular necrosis was worse in PtcLacZ mice than WT mice after BDL.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[73][74][75] Immunohistochemistry of BDL livers demonstrated that some bile ductular cells expressed Ptc and Gli-2, suggesting that relatively immature liver epithelial cells are Hh targets. Our in vitro studies support this concept because, under our culture conditions, the Ptc-( þ )ve cholangiocyte line coexpressed several oval cell markers, mpk and c-kit, [44][45][46][47] and the immature cholangiocyte marker, N-CAM, 3,43,76,77 as well as markers of more mature cholangiocytes (ie, aquaporin-1 and CK-19). If further research verifies that Hh signaling promotes the outgrowth of relatively immature liver epithelial cells, this might explain why patchy lobular necrosis was worse in PtcLacZ mice than WT mice after BDL.…”
Section: Discussionsupporting
confidence: 66%
“…Notably, however, under our culture conditions, these cholangiocytes also expressed several markers of immature bile ductular cells, including neural markers (eg, NCAM), 43 muscle pyruvate kinase (mpk), 44 and c-kit. 45 The latter transcripts were also demonstrated in oval cells, which are known to coexpress neural, smooth muscle and progenitor markers. [44][45][46][47] These data suggest that Hh pathway activity occurs in immature cholangiocytes (ie, bile ductular cells).…”
Section: Hh Signaling Increases After Bile Duct Ligationmentioning
confidence: 97%
See 1 more Smart Citation
“…hepatoblasts in normal liver development and oval cells in injured adult organ), as far as we know, give exclusively an epithelial progeny. Several authors have also suggested the possibility that HCS themselves can differentiate into hepatocytes; [18][19][20][21] recent works have demonstrated this in culture 22 and in vivo with a fate-mapping approach, 23 thus suggesting that quiescent HSC could be a component of the progenitor compartment in adult liver.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 These findings support the concept that the ductular reaction represents an expansion of the progeny of typically inconspicuous liver progenitors that reside along Canals of Hering in healthy adult livers and suggest that the ductular reaction is involved in liver repair. 8 Fortunately, knowledge about the mechanisms that regulate the ductular response to liver injury is growing [9][10][11][12][13] because such information might suggest novel therapeutic targets to reduce fibrosis and improve regeneration in individuals with alcoholinduced liver injury.…”
mentioning
confidence: 99%